Teachers' Efforts in Developing Fine Motor Skills in Early Childhood - Vivi Suryandari; Leli Fertiliana Dea; Isnaini Nur Azizah (Bulletin of Early Childhood, 2025)
This research is motivated by the importance of fine motor development in early childhood, especially 5-6 years old, because this ability plays an important role in supporting children's learning activities. However, the fine motor skills of children at Rohman Nur Islamic Kindergarten, Natar District, have not yet developed optimally, as seen from several children who have difficulty in buttoning clothes, cutting, folding paper, and holding colored pencils properly. Therefore, it is necessary to use interesting learning media that are appropriate to the characteristics of children, one of which is sawdust which has a light texture, is easy to shape, and is easily found in the surrounding environment. This study aims to determine the efforts of teachers in developing fine motor skills in children aged 5-6 years through sawdust media. This study uses a qualitative method with a descriptive type, with 21 subjects consisting of 6 children who have not developed, 9 children who are starting to develop, and 6 children who are developing as expected. Data collection techniques are carried out through observation, interviews, and documentation, then analyzed through the stages of data collection, data presentation, and drawing conclusions. The research results show that teachers' efforts through careful planning, the use of appropriate learning methods and media, guidance, and ongoing evaluation can significantly improve children's fine motor development, reaching the expected development category. Therefore, the use of sawdust can be an effective alternative learning medium to support the fine motor development of early childhood.